Architecture in daily functioning of disabled people with special emphasis - Piotr Gleń; Aleksandra Jarocka-Mikrut (Budownictwo i Architektura, 2015)
This article aims to stir the problem of obstacles and inconveniences faced by people with disabilities (including with reduced mobility , elderly , deaf , visually impaired and blind). The aim is to draw attention to the role played by the designer , both the architect and creator of utilitarian objects in shaping the impact on the comfort of living together in society of people with a complete physical and disabled. The need for education and promote greater awareness of these " dysfunctions " should be developed through places where non-disabled person is able to face the everyday barriers disabled person. An important aspect is to create awareness architect in the field of universal design at the stage of studies. More attention should focus on the design of everyday objects for the disabled so as not to have to change them later by artificial means. The article focuses on the problems and the positive examples of solutions in the process of shaping the architecture tailored to the needs of such people. The aim is also analysis of urban solutions that favor their functioning in everyday life. The authors are also examples of architectural and urban planning from both the Polish and the world. They show the importance and contribution of the architect in creating private and public spaces that surround us every day.